Quantitative Assay Method for Starch Branching Enzyme with Bicinchoninic Acid by Measuring the Reducing Terminals of Glucans - Utsumi, Yoshinori; Nakamura, Yasunori; Francisco, Perigio B., Jr; Sawada, Takayuki; Yoshida, Mayumi; Kitamura, Shinichi (Journal of Applied Glycoscience, 2009)
A reliable quantitative assay method for starch branching enzyme (BE) remains to be established whereas it has been required to characterize BE towards understanding the regulatory mechanism for the synthesis of starch in plant tissues. We describe a new quantitative assay method for BE activities with malto-oligosaccharides, amylose and amylopectin as substrates by using bicinchoninic acid (BCA) for measuring directly the reducing terminals of linear glucans formed after debranching the reaction products. The BCA method not only can be performed by simple procedures and easy handling with the use of cheap toxic-free reagents, but also shows highly color-stable properties after the treatment of the reaction mixture with the color-yielding reagents compared with the modified Park-Johnson method (Carbohydr. Res., 94, 205-213(1981)). The intensity and the spectrum of the purple color generated in the treated assay mixture are maintained in sugars and glucans in the range of glucose and amylose with degree of polymerization up to at least 1658. The BCA method can be also applied for characterization of BE when amylopectin is used as glucan substrate. In this paper we report this efficient, reproducible and quantitative BCA method by showing some experimental results obtained in an attempt to determine the kinetic parameters of BEIIb from rice endosperm.